A Sustainability Interrogation of the Autonomous Vehicle at Its Society-Technology Interface. (October 2019) - Martin, George
This analysis of the emergent automated vehicle technology focuses on the friction at its interface with society, clouding its future. The sequential focus of development → deployment is reconfigured as reciprocal: society ↔ technology. A best path forward is presented that incorporates environmental and social sustainability factors as they relate to climate change and public health. The path's signpost is automated electric vehicles deployed in public and private fleets. This course has promise to recover automobility from the damaging, unsustainable legacy of personal internal combustion vehicles—highlighted by their toxic and carbon emissions, and road casualties.